The Opercular-Subopercular Syndrome: Four Cases with Review of the Literature - M. Bakar; H. S. Kirshner; F. Niaz (Behavioural Neurology)
We present four cases of the ‘opercular syndrome’ of volitional paresis of the facial, lingual, and laryngeal muscles (bilateral facio-glosso-pharyngo-masticatory paresis). Case histories and CT brain images are presented, along with a review of the literature concerning this long-recognized but little-known syndrome. The neuroanatomic basis of the syndrome classically involves bilateral lesions of the frontal operculum. We propose, on the basis of our cases and others, that the identical syndrome can arise from lesions of the corticobulbar tracts, not involving the cortical operculum. Our cases included one with bilateral subcortical lesions, one with a unilateral left opercular lesion and a possible, non-visualized right hemisphere lesion, one with unilateral cortical and unilateral subcortical pathology, and one with bilateral cortical lesions. These lesion localizations suggest that any combination of cortical or subcortical lesions of the operculum or its connections on both sides of the brain can produce a syndrome indistinguishable from the classical opercular syndrome. We propose the new term ‘opercular-subopercular syndrome’ to encompass cases with predominantly or partially subcortical lesions.